Infant with a sudden, large, post-extubation subglottic cyst - Asha'ari, Zamzil Amin; Yusof, Suhaimi; Abdullah, Ahmad Fadzil; Zihni, Muhammad (Universiti Sains Malaysia, 2012)
Acquired subglottic cyst in infancy is almost always associated with episodes of early life intubation. Most cases typically presented late, usually days to months after extubation. We report a case of a subglottic cyst with different presentation than the norm. This case highlights that subglottic cyst can present acutely, and rapidly enlarging soon after the airway extubation. As the management of a large subglottic cyst can be challenging, a close observation for early diagnosis and intervention are recommended post extubation in the high-risk cases, such as in the premature infant.